PRODUKTIVITAS CAISIM (Brassica juncea, L.) AKIBAT PENGOLAHAN TANAH DAN FREKUENSI PENANAMAN - Budi Sambodo; Gembong Haryono; Yulia Eko Susilowati (JURNAL VIGOR, 2016)
Research on productivity caisim (Brassica juncea, L.) due to cultivation soil and frequency of planting, conducted from May to August 2015 in the village of Lebak District Grabag, Magelang. Altitude of 500 meters with Latosol soil type and soil pH 6. The research was conducted in a factorial experiment ( 3 x 3 )arranged in a complete randomized block design with three replications. The first factor is tillage frequency: once, twice and three times. The second factor is the frequency of replanting: the first,second, and third planting. The result showes that tillage do not influence crop yields. Frequencies of replanting increase the number of leaves and fresh weight of consumption per plot. Tillage frequency on planting frequency responded similarly to the parameters.